KEY SUCCESS FAKTOR KINERJA KEUANGAN DENGAN ANALISIS RASIO UNTUK MEWUJUDKAN EFEKTIVITAS POTENSI PENERIMAAN ASET DAERAH - Desi Susilawati; Intan Fajar Rahmawati; Rizka Arum Rachmayanti (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
The success in the practice of regional autonomy comes from the hard work of Regional Government in dutifully conducting financial management in accordance by the law. The problem faced in managing regional finance is the condition where certain regional potential financial resources have not been maximized. It is a fact that the budget of Sleman Regency still depends on the funding from Central Government. This research aims to measure the independence of regional government in practicing regional autonomy in Sleman Regency by assessing the financial performance Badan Keuangan dan Aset Daerah (BKAD) based on the Budget Realization Report (LRA) for five years from 2012-2016 by analyzing the effectiveness and PAD efficiency ratio and growth ratio. This research different to others, because we briefly describe another aspect used to measure the performance of regional government is by using the effectiveness and contribution of Land and Building Tax (PBB) income ratio, as an original regional income source, it will contribute to the regional financial performance. The result of this research shows that the relationship pattern of regional government independence is considered not independent enough, but the level of financial management efficiency is considered efficient. The degree of fiscal decentralization is considered sufficient because the realization of PAD income is very effective, However the level of regional financial dependency toward central government is considered very high. One of the factors is due to lack the contribution from Land and Building Tax Income to PAD. This situation is caused by ineffective Land and Building Tax income. The growth ratio shows that the ability of Sleman Regency Government in maintaining and improving success fluctuates. Keywords: self-sufficiency ratio, effectiveness ratio, the contribution of Land and Building Tax